Acute Activation of the Renal Betaine/GABA Transporter in Response to a Decrease in Extracellular Calcium. (5th November 2012) - Parikh, Nehal R.; Vaughn, Cherissa L.; Williams, Lagina L.; Kempson, Stephen A.
Abstract : The betaine/GABA transporter (BGT1) is important for osmoprotection in kidney medullary cells. We previously reported an acute (30 min) increase in extracellular Ca 2+ caused dose dependent inhibition of BGT-1 in renal MDCK cells. To determine if extracellular Ca 2+ might be a local regulator of BGT-1, we have tested the response to low Ca 2+ serum-free growth medium (LCM, 0.05 mM Ca 2+ ). Chronic treatment (8–24 h) of MDCK cell monolayers completely blocked hypertonic adaptation of BGT1 and disrupted tight junctions. In contrast, acute treatment activated BGT1 transport within 30 min in MDCK cells previously adapted to hypertonic growth medium containing normal Ca 2+ (1.6 mM). Activation was significant after 60–90 min and was independent of medium osmolarity. Peak transport was increased 50% in isotonic LCM and 100% in hypertonic (500 mOsm) LCM over controls. The activation was reversed by restoration of normal Ca 2+ . Perfusion of Fura-2-loaded MDCK cells with LCM decreased intracellular Ca 2+ by 31% within 6-7 min. Inclusion of staurosporine (0.6  μ M), a protein kinase C inhibitor, potentiated the action of LCM. We suggest that activation of BGT1 by LCM may be due in part to inhibition of protein kinase C.